Kontekstualisasi Pembagian Warisan 2:1 Perspektif Mubadalah : Efforts to Find the Meaning of Equality in Islamic Family Law in Indonesia - Muhammad Asyrofudin; Rahmad Setyawan; Khairuddin; Muhammad Adib Samsudin; Ulum Ahmad Adnani (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2025)
This article revisits the 2:1 inheritance distribution between men and women through the perspective of mubadalah to find the meaning of equality in Islamic Family Law in Indonesia. This study uses library research methods, with data sources from the Qur'an, hadith, classical fiqh books, tafsir works, contemporary literature, journal articles, and the thoughts of modern scholars on inheritance and gender issues. The analysis was conducted in three steps: 1) examining classical fiqh concepts and the theological basis for the 2:1 inheritance distribution rule; 2) contextualizing the social conditions of early Islamic Arab society with the socio-economic realities of modern Indonesian society; and 3) applying the mubadalah interpretation method as an analytical framework to understand the inheritance verses more substantively. The results of this study show that the 2:1 provision is not an absolute rule, but rather a formulation that arose from the social and cultural structure of early Islamic society. Through the principles of reciprocity, justice, and gender equality, the mubadalah interpretation opens up space for reinterpreting inheritance law to be more adaptive to social and economic dynamics and gender roles in Indonesia. This reinterpretation is a practical necessity for realizing substantive justice in Islamic Family Law, especially when women contribute significantly to family and community life. Thus, reinterpreting the 2:1 inheritance rule is not merely a normative academic discourse but a practical necessity to uphold the values of equality and benefit in Islamic family law in Indonesia, and is in line with the main objectives of Sharia (maqāṣid asy-syarī‘ah) in realizing justice and humanity.